Promoting reflective learning and empowerment through youth coaching - Petra Røise (European Teacher Education Network, 2018)
Some young people face challenges in managing society's individualized freedom of choice and requirements. In relation to this context, youth coaching methodology is developing. Knowledge is needed on how coaching can facilitate youth empowerment through reflective learning. In-depth interviews with three youth coaches were conducted and related to a strategic search for literature. Analysis identified three topics; empowerment through collaboration, the ethical boundaries of a coaching contract and coaching to strengthen reflective learning. Aspects influencing the collaborative partnership between coach and young person need to be considered.